Factors Associated With Experiences of Fear, Anxiety, Depression, and Changes in Sleep Pattern During the COVID-19 Pandemic Among Adults in Nigeria: A Cross-Sectional Study - Morenike Oluwatoyin Folayan; Morenike Oluwatoyin Folayan; Olanrewaju Ibigbami; Brandon Brown; Brandon Brown; Maha El Tantawi; Maha El Tantawi; Nourhan M. Aly; Nourhan M. Aly; Oliver C. Ezechi; Oliver C. Ezechi; Giuliana Florencia Abeldaño; et al. (Frontiers Media S.A., 2022)
BackgroundMultiple facets of the pandemic can be a source of fear, depression, anxiety and can cause changes in sleep patterns. The aim of this study was to identify health profiles and the COVID-19 pandemic related factors associated with fear, depression, anxiety and changes in sleep pattern in adults in Nigeria.MethodsThe data for this analysis was extracted from a cross-sectional online survey that collected information about mental health and well-ness from a convenience sample of adults 18 years and above resident in Nigeria from July to December 2020. Study participants were asked to complete an anonymous, closed-ended online questionnaire that solicited information on sociodemographic profile, health profiles (high, moderate and low COVID-19 infection risk profile) including HIV status, COVID-19 status, and self-reported experiences of fear, anxiety, depression and changes in sleep patterns.ResultsIn total, 4,439 participants with mean age of 38.3 (±11.6) years responded to the survey. Factors associated with higher odds of having COVID-19 related fear were health risk (p < 0.05); living with HIV (AOR: 3.88; 95% CI: 3.22-4.69); having COVID-19 symptoms but not tested (AOR: 1.61; 95% CI: 1.30-1.99); having a friend who tested positive to COVID-19 (AOR: 1.28; 95% CI: 1.07-1.53) and knowing someone who died from COVID-19 (AOR: 1.43; 95% CI: 1.24-1.65). The odds of feeling anxious was significantly higher for those with moderate or low health risk profile (p < 0.05); living with HIV (AOR: 1.64; 95% CI: 1.32-2.04); had a friend who tested positive for COVID-19 (AOR: 1.35; 95% CI: 1.08-1.68) or knew someone who died from COVID-19 (AOR: 1.53; 95% CI: 1.28-1.84). The odds of feeling depressed was significantly higher for those with health risk profile (p < 0.05); living with HIV (AOR: 2.49; 95% CI: 1.89-3.28); and respondents who had COVID-19 symptoms but had not taken a test (AOR: 1.41; 95% CI: 1.02-1.94). Factors associated with higher odds of having sleep pattern changes were having moderate and low health risk profiles (p < 0.05).ConclusionThe study findings suggest that the pandemic may cause fear, anxiety, depression and changes in sleep patterns differently for people with different health profile, HIV status and COVID-19 status.